2023
DOI: 10.3390/jcm12051949
|View full text |Cite
|
Sign up to set email alerts
|

Usability of an Embodied CAVE System for Spatial Navigation Training in Mild Cognitive Impairment

Abstract: Individuals with mild cognitive impairment (MCI) usually report navigation and spatial memory impairments. Spatial navigation is an embodied process that requires the active involvement of both physical (e.g., motor commands and proprioception) and cognitive (e.g., decision-making and mental rotation) information. Immersive virtual reality (IVR) is a valuable tool that employs this information as real-world navigation does. Given the crucial impact of spatial navigation on daily life, research should focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The ANTaging semi-immersive condition also improved when compared to the CAVE system (prototype). Similarly to the previous study (Tuena et al, 2023), our findings demonstrated that, beyond graphical elements, older people with MCI place significant importance on psychological factors, notably their perceived confidence in using a new technological device (e.g., 3dRudder). This aligns perfectly with established technology acceptance models within the context of aging (Contreras-Somoza et al, 2021).…”
Section: Vr Environment Preferencessupporting
confidence: 84%
See 2 more Smart Citations
“…The ANTaging semi-immersive condition also improved when compared to the CAVE system (prototype). Similarly to the previous study (Tuena et al, 2023), our findings demonstrated that, beyond graphical elements, older people with MCI place significant importance on psychological factors, notably their perceived confidence in using a new technological device (e.g., 3dRudder). This aligns perfectly with established technology acceptance models within the context of aging (Contreras-Somoza et al, 2021).…”
Section: Vr Environment Preferencessupporting
confidence: 84%
“…Importantly, we report in Table 7 a comparison of SUS and ITC-SOPI negative effects of the old ANTaging CAVE version ( Tuena et al, 2023 ) and the improved prototype we tested here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of visual interfaces is used to create varying degrees of immersion in a virtual environment, ranging from conventional monitors to head-mounted displays [39]. Immersion, where the user is surrounded by the virtual environment, is a crucial feature that distinguishes VR systems used in rehabilitation into immersive and non-immersive categories [41].…”
Section: Discussionmentioning
confidence: 99%
“…The former may include landmark recognition and sorting or asking participants to travel a previously learned route. The latter may include map-drawing and shortcut tasks [16,17].…”
Section: Spatial Navigation Processesmentioning
confidence: 99%